Health programmes logistics and international aid in Nepal: an overview of processes improvements. Issue 2 (7th March 2016) - KC, Bhuvan; Heydon, Susan; Norris, Pauline
Abstract: Objectives: The objective of this review was to describe the development of health logistics in Nepal, processes that led to this development and the contribution made by international aid. Methods: We performed a literature search using search engines Google Scholar, Web of Science and PubMed using the keywords 'Health logistics AND Nepal' and collected 54 articles most of which could be described as 'grey literature'. We also communicated with key informants and collected 30 articles on the health logistics system and development in Nepal and involvement/contribution of various stakeholders. Some 26 articles suggested by the key informants were already included in the review. Thus, we compiled a total of 58 articles, categorised them and selected 10 articles related to Nepal. This was then analysed to depict health programmes logistics and international aid in Nepal. Key findings: Health logistics development in Nepal has been possible through sustained policy focus, cooperation and support from the international aid agencies and better implementation. It has been the backbone of the successfully implemented public health programmes. However, the challenge is to withstand the growing demand to deliver product and services. Conclusions: International aid agencies have been supportive and instrumental in setting up the health logistics management system in Nepal, but the onus now is on the Nepalese government to create a sustainable and decentralised logistics management system that relies on the technical capabilities and network of its own people, institutions and organisations.